EFEKTIVITAS PENGGUNAAN VIDEO DIGITAL STORYTELLING PADA MATERI TRIGONOMETRI DI KELAS X UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Endang Krisnawati; Denok Julianingsih (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2019)
This study aims to find out: (1) differences in student motivation between learning using digital video storytelling and learning without using digital video storytelling (2) the effectiveness of using digital video storytelling in trigonometric learning. This research is an experimental study using true experimental design with a pre test-post test control group design model. This research was conducted at SMA Muhammadiyah 4 Surabaya with samples taken of two classes used for the experimental class and the control class. The technique of collecting data uses student learning motivation questionnaires. While the analysis technique used is descriptive statistics and inferential statistics. The results showed there were differences in student learning motivation using digital video storytelling and those not using digital video storytelling. The difference can be seen from the average value of student learning motivation in the experimental class before the use of media by 28.44 and after using media by 47.48. In addition, research results from the results of the Mann-Whitney Test show that the use of digital video storytelling media is effectively used in trigonometric learning. This is evidenced from the average results of student motivation in the experimental class increased by 19.04 while the average student motivation in the control class increased by 11.07. Seen an increase in student motivation in classrooms using digital video storytelling is higher than those who do not use digital video storytelling.